Performance Measurement of Small and Medium Enterprise from "Wirausaha Muda Mandiri" Contestant - Tumbuan, James Evan; Hudrasyah, Herry (Journal of Business and Management, 2014)
Asbrtract- In order to become a developed country, Indonesia needs approximately 12 million entrepreneurs to fulfill the requirement that developed countries of at least 2% of the population are entrepreneurs. Bank Mandiri as a Government Bank makes a company social responsibility programs such as Wirausaha Muda Mandiri. Wirausaha Muda Mandiri awarded to young entrepreneurs who succeed in business. This program is success to increase the interest of young people to become entrepreneur and hoped young generation can success in business field.WMM has produced young entrepreneurs since 2007. Since 2007 there’s no measurement who measure the Wirausaha Muda Mandiri Performance. By using Strategic Factor Analysis Summary, this research aims to determine the performance of the Young Entrepreneur duo mainly regional winners in 2012 .After interviewing eight regional winners and by using the theory of Strategic Factor Analysis Summary showed that 3 of the 8 winners WMM has a below average value and potential bankruptcy. The results obtained are also the majority of these young entrepreneurs have the core competencies to compete. Unfortunately they do not have good cash flow and capital usually mixed up with owner’s money. Keyword: Wirausaha Muda Mandiri, Young entrepreneur, Developed Country, Strategic Factor Analysis Summary, Indonesia.